Sinergi Pelayan dan Jemaat Tuhan Menurut 1 Korintus 3:4-9 - Desti Ratna Sari Halawa (CARAKA: Jurnal Teologi Biblika dan Praktika, 2021)
AbstractThis paper examines the meaning of synergy in the ministry and life of believers according to 1 Corinthians 3: 4-9. Servants of God tend to leave the place of service because they are at odds with God or others. Among the Corinthians in the early church, there was strife among the members of the body of Christ. To deal with divisions, Paul talks about becoming partners with God (synergy). In the Orthodox  church this concept emphasizes how to achieve salvation but this concept is not emphasized in the world of ministry. Whereas in Protestant literature this concept is rarely even perhaps foreign to be discussed as something important, so that it is reflected in ministries within the church and outside the church which often cause divisions. The results show that only through synergy with God can humans synergize with one another (one with God and one with others remains strong). Synergize is to be partners with Allah who continue to exercise their free will according to God's will so that they are not easily tempted by the evil of sin. Remembering God dynamically produces union with God and gives the best service to others as Christ served. Of course, only synergy makes humans avoid fellowship and enmity between others. AbstrakTulisan ini meneliti makna sinergi dalam pelayanan dan kehidupan orang percaya menurut 1 Korintus 3:4-9. Pelayan Tuhan cenderung meninggalkan tempat pelayanan karena berselisih dengan Allah atau sesama. Di antara jemaat Korintus di masa gereja mula-mula perselisihan di antara anggota tubuh Kristus sudah terjadi. Untuk menghadapi perpecahan, Paulus berbicara bagaimana menjadi kawan sekerja Allah (sinergi). Dalam gereja Ortodoks konsep ini menekankan bagaimana mencapai keselamatan akan tetapi konsep ini tidak ditekankan dalam dunia pelayanan. Sedangkan dalam literatur Protestan konsep ini jarang bahkan mungkin asing dibahas sebagai sesuatu yang penting, sehingga tercermin dalam pelayanan-pelayanan dalam gereja maupun di luar gereja yang sering menimbulkan perpecahan. Hasil penelitian menunjukkan bahwa hanya melalui sinergi dengan Allah manusia bisa bersinergi dengan sesamanya (menyatu dengan Allah dan persatuan dengan sesama tetap kokoh). Bersinergi adalah menjadi kawan sekerja Allah yang terus melatih kehendak bebasnya sesuai dengan kehendak Allah sehingga tidak mudah tergoda oleh kejahatan dosa. Mengingat Allah secara dinamis menghasilkan persatuan dengan Allah dan memberi pelayanan terbaik kepada sesama seperti Kristus melayani. Tentunya, hanya sinergilah yang membuat manusia terhindar dari persekutuan serta permusuhan di antara sesama.